Diseño de un sistema de filtración continua arena - carbón activado como herramienta didáctica en el laboratorio de operaciones unitarias (2018)
In the present work a continuous filtration system of sand and activated carbon was designed, in order to propose this equipment as a pedagogical tool for future implementation, for the learning of the filtration processes, inthe operating laboratory of the University San Buenaventura de Cartagena. The methodology used was projective, which involved exploring, describing, explaining and proposing alternatives for change. In order to reach the proposed objective, an area study was carried out, a theoretical review of designs proposed by other authors and an analysis of economic feasibility. According to the results obtained, the proposed design will allow to work with two filters simultaneously in the laboratory of unit operations varying the activated carbon to a thickness of 5 cm, with the purpose of establishing which of both filters would present better levels of water purification. From which it was possible to conclude, that the proposed system would be useful as a didactic tool, to evaluate key concepts such as filtration, absorption, in addition to the manipulation and variation in the thickness of the materials of the same. The costs of activated carbon, gravel and sand are affordable for acquisition. On the other hand, expenses can be reimbursed for the benefits that the project provides, such as the recovery of contaminated water that can be reused in various tasks that are required at the University.